On artificial intelligence as an instrument: The cognitive dependency argument - Aguirre Franco, Marcos de J. (Analysis. Journal of Philosophical Research, 2024)
For various reasons, the philosophers Hubert Dreyfus and John Searle disagree on the possibility that AI is capable of thinking and understanding as humans do. Both the enactivism of Dreyfus (1992) and the semantic position of Searle (1980) serve as the basis for the thesis of cognitive dependence defended here, which considers that AI is incapable of developing its own functions without the support of the cognitive abilities that derive from the creativity and experience of living beings, especially human life.